2020
DOI: 10.21203/rs.3.rs-80063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A real world retrospective observational study exploring the effectiveness and safety of antifibrotics in idiopathic pulmonary fibrosis

Abstract: Background Pirfenidone and nintedanib are the only disease-modifying treatments available for idiopathic pulmonary fibrosis (IPF). Our aim was to test their effectiveness and safety in clinical practice.Methods This is a single centre retrospective observational study undertaken at a specialised interstitial lung disease centre in England. Data including progression-free survival (PFS), mortality and drug tolerability were compared between IPF patients on antifibrotic therapies and an untreated control group w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Of the 16 studies reviewed, we found that 14 studies were detected with presence of ITB based on the ITB checklist, while there were insufficient data for assessment of two others. This is consistent with a recently published Letter to Editor (26) that summarized observational studies reporting the effectiveness of antifibrotic therapy on mortality of IPF and identified 14 studies (16-19, 35,41,42,44,45,[53][54][55][56][57] presenting ITB. Compared to a previous study (26), we have included more studies and have provided more detailed information by using the ITB checklist and conducting a simulation study to identify and account for ITB in IPF studies.…”
Section: Identification Of Itbsupporting
confidence: 88%
“…Of the 16 studies reviewed, we found that 14 studies were detected with presence of ITB based on the ITB checklist, while there were insufficient data for assessment of two others. This is consistent with a recently published Letter to Editor (26) that summarized observational studies reporting the effectiveness of antifibrotic therapy on mortality of IPF and identified 14 studies (16-19, 35,41,42,44,45,[53][54][55][56][57] presenting ITB. Compared to a previous study (26), we have included more studies and have provided more detailed information by using the ITB checklist and conducting a simulation study to identify and account for ITB in IPF studies.…”
Section: Identification Of Itbsupporting
confidence: 88%